FBXL4-related encephalomyopathic mitochondrial DNA depletion syndrome: A rare cause of hyperammonemia - Ayça Burcu Kahraman; Halil Çelik; Zafer Bagci; Abdullah Sezer; Mustafa Kılıç (Molecular Genetics and Metabolism Reports)
Introduction: FBXL4- related encephalomyopathic mitochondrial DNA (mtDNA) depletion syndrome is caused by pathogenic variants in the FBXL4 gene, resulting in mitochondrial dysfunction and multisystem involvement. Hyperammonemia is reported in 45 % of cases but extremely elevated ammonia levels are rare. Case presentation: A male infant presented with dysmorphic features, hypotonia, failure to thrive, and lactic acidosis and severe hyperammonemia (ammonia: 1495 μmol/L). Genetic testing identified a homozygous FBXL4 pathogenic variant. Conclusion: To our knowledge, this report presents a neonatal case of FBXL4-related mtDNA depletion syndrome with the highest hyperammonemia level. This case emphasizes the importance of FBXL4 genetic testing in neonates with multisystem involvement, hyperammonemia, and dysmorphic features.